Maternal and neonatal referral system in rural North Lampung: a qualitative study of referral system readiness - Lisa Suarni; El Rahmayati; Kodri Kodri (PAGEPress Publications, 2024)
A reliable referral system is the key to handling emergency cases, for this reason, it is necessary to conduct an in-depth study of the description of the referral system that is in force and implemented in North Lampung, considering that most maternal deaths are caused by cases that require fast and integrated treatment. The aim of the research is to provide an overview of the readiness of the maternal neonatal referral system in terms of four aspects: i) infrastructure, ii) human resources readiness, iii) community readiness, and iv) policy readiness. The research is using qualitative analysis. Data collection uses in-depth interviews, documentation studies, observations, and Focus Group Discussions (FGDs). The Maternal Mortality Rate (MMR) is impacted by the quality of maternal and neonatal services, including handling pregnancy complications. The percentage of rural North Lampung who gained coverage for focusing on pregnancy issues throughout 2021 was a miserable 52.66%. Rural North Lampung's pregnancy-related issues procedures do not adhere to the operational guidelines for maternal-neonatal referral procedures. The fundamental reference, Educate Basic Emergency Neonatal Obstetric (BEmONC), is no longer in operation, as is Comprehensive Emergency Neonatal Obstetric Services (CEmONC). The readiness of all stakeholders for the neonatal and maternal referral system needs to be improved, including the readiness of infrastructure, human resources, and family-community readiness, and needs to be supported by regional government policies.